2020
DOI: 10.1101/lm.052316.120
|View full text |Cite
|
Sign up to set email alerts
|

Motivational factors underlying aversive Pavlovian-instrumental transfer

Abstract: While interest in active avoidance has recently been resurgent, many concerns relating to the nature of this form of learning remain unresolved. By separating stimulus and response acquisition, aversive Pavlovian-instrumental transfer can be used to measure the effect of avoidance learning on threat processing with more control than typical avoidance procedures. However, the motivational substrates that contribute to the aversive transfer effect have not been thoroughly examined. In three studies using rodents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Aversive Pavlovian Instrumental Transfer (PIT; also referred to as transfer-of-control paradigms) is nearly identical to conditioned suppression, in that animals receive separate Pavlovian and instrumental training in separate phases. However, the main difference is that the test phase (transfer) occurs under extinction (Campese et al, 2013(Campese et al, , 2020Cartoni et al, 2016;Estes, 1943). Specifically, during the test (transfer) phase, the animal is presented with the Pavlovian CS in extinction (e.g., tone but no shock) while they perform the instrumental task (Scobie, 1972).…”
Section: Aversive Pavlovian Instrumental Transfer (Pit)mentioning
confidence: 99%
“…Aversive Pavlovian Instrumental Transfer (PIT; also referred to as transfer-of-control paradigms) is nearly identical to conditioned suppression, in that animals receive separate Pavlovian and instrumental training in separate phases. However, the main difference is that the test phase (transfer) occurs under extinction (Campese et al, 2013(Campese et al, , 2020Cartoni et al, 2016;Estes, 1943). Specifically, during the test (transfer) phase, the animal is presented with the Pavlovian CS in extinction (e.g., tone but no shock) while they perform the instrumental task (Scobie, 1972).…”
Section: Aversive Pavlovian Instrumental Transfer (Pit)mentioning
confidence: 99%
“…PIT describes a phenomenon by which a classically conditioned stimulus (CS) influences instrumental responding, or in a broader sense, how one's operant behavior is modulated by environmental cues [5][6][7]. Appetitive and aversive CSs are frequently utilized to elicit PIT effects [8][9][10][11], which can be quantified by various behavioral and motivational measures. Appetitive cues have previously been shown to induce approach behavior, while aversive cues tend to induce withdrawal behavior.…”
Section: Introductionmentioning
confidence: 99%
“…When subsequently presented while the dogs were engaged in shuttling, the tone increased the rate of responding (Rescorla & Lolordo, 1965). It is unlikely that increase was due an expectation of a shock during the tone because LoLordo subsequently demonstrated that a signal for a loud aversive klaxon produced as great an elevation of shock-reinforced avoidance responding by the dogs (LoLordo, 1967), a finding recently replicated with rats (Campese et al, 2020). Rather it would appear that the avoidance PIT reflects a general motivating effect of aversive signals.…”
Section: Discussionmentioning
confidence: 98%